Dinosaur hunter Robert Irwin. Written by Jack Wells - Irwin, Robert 2003- (Random House Australia, 2013)
Discover a world of prehistoric dinosaur adventure with Robert Irwin! While on a visit to the Canadian Badlands, Robert and his best friend Riley gets pulled back in time to Alberta, Canada during the late Cretaceous period. They also have to avoid a ferocious gorgosaurus looking for a snack while trying to rescue a trapped euoplocephalus